An Improved Model for Circular RNA Overexpression: Using the Actin Intron Reveals High Circularization Efficiency - Feiya Li; Juanjuan Lyu; Yang Yang; Qiwei Yang; Cristian Santos; Burton B. Yang (Advanced Genetics, 2023)
Abstract Traditionally, the group 1 intron of the T4 td gene is used to generate a foreign circular sequence. However, the T4 system has been shown to be fairly inefficient in expressing circular RNA (circRNA). Here, a new method is developed to express circular sequences with high circularization efficiency to strengthen the confidence for future circRNA functional studies. CircRNA expression plasmids, constructed with different lengths derived from the actin intron (15‐nt, 30‐nt, 60‐nt, 100‐nt, 180‐nt) and T4 intron, are introduced into human and mouse cell lines 293T and B16. Junction detection and sequencing are used to determine successful circularization of introns and their expression efficiencies. An actin intron with a medium length (60‐nt–100‐nt) shows significantly increased efficiency of circularization, whereas intron‐100‐nt shows the best efficiency in most conditions. RNA pull‐down assays are designed to precipitate the splicing factors that are bound to the introns and intron/exon junction. The precipitated proteins are analyzed by mass spectrometry (MS), aiming to identify the possible underlying mechanism behind the high circularization efficiency. This expression system has been validated using different circRNAs, and such method shows potential in contributing to the expanding field of circRNA studies.